On bare and non-bare temporal names in Romanian - Mihaela Tănase-Dogaru (LingBaW)
The present paper investigates punctual vs. habitual readings of Romanian proper temporal names of the type luni ‘Monday’ vs. lunea ‘Monday.def’. These readings are associated with the absence vs. presence of the definite article (Franco and Lorusso 2022). The paper makes two major claims. Firstly, following Longobardi (1994, 2005), and Franco and Lorusso (2020), the paper claims that with bare, i.e., definiteless, proper time names, N-to-D movement triggers individual-like reference, which, in turn, explains why the event is interpreted as punctual. Secondly, the paper shows that the structure of proper temporal names is complex, in the sense that it contains the classifier zi ‘day’, thus paralleling the structure of complex descriptive proper names of the type ‘the planet Venus’ (see van Riemsdijk 1998, Cornilescu 2007 a.o.). This classifier is shown to be overt when there is no N-raising, and silent when N raises to D in the structure of proper temporal names.